ANALISIS PENDAPATAN USAHA COKELAT OLAHAN PADA INDUSTRI UKM SAKAYA DI KOTA PALU - Didin Palamma; Sulaeman Sulaeman (Universitas Tadulako, 2022)
Cocoa (Theobroma cacao L) is a cultivated tree originating From South America, from which cocoa beans are produced a processed product known as chocolate when developed throungh the Agro-industry. One of the well-known industries in Palu City today is the Sakaya SME Industry. The Sakaya UKM Industry produces unique chocolate products both in taste, packaging from, in terms of type, and the distinctive aroma of the chocolate. This study aims to determine how much the income level of the chocolate business in the Sakaya BTN Pengawu, West Palu, Palu City in January 2020. The thetermination of respondents in this study was carried out purposively, the selected respondents were owners and employees from both the production and marketing departements of the industry. Sakaya UKM. The data used in this research comes from primary data and secondary data. The analysis used is Income analysis. The results showed that the income earned in November and December 2019 was Rp. 16.958.751. For Conventure chocolate. Convecture chocolate is produced every month according to consumer demand. From November to December, Convecture chocolate Demand was made so that the 2019 Sakaya UKM’s Conventure Chocolate income was quite good.